2003
DOI: 10.1095/biolreprod.102.011791
|View full text |Cite
|
Sign up to set email alerts
|

γ-Tubulin Overexpression in Sertoli Cells In Vivo: I. Localization to Sites of Spermatid Head Attachment and Alterations in Sertoli Cell Microtubule Distribution1

Abstract: Sertoli cells play a number of roles in supporting spermatogenesis, including structural organization, physical and paracrine support of germ cells, and secretion of factors necessary for germ cell development. Studies with microtubule disrupting compounds indicate that intact microtubule networks are crucial for normal spermatogenesis. However, treatment with toxicants and pharmacologic agents that target microtubules lack cell-type selectivity and may therefore elicit direct effects on germ cells, which also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Furthermore, studies specifically targeting microtubules within SCs, such as SC-specific over-expression of the microtubule nucleating protein, gamma-tubulin [11], [12], or SC-specific expression of a dominant-negative form of the microtubule plus end binding protein EB1 [13] induce similar germ cell loss from the seminiferous epithelium. Together these studies demonstrate that SC microtubule-dependent functions are extremely sensitive to aberrant microtubule remodelling.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies specifically targeting microtubules within SCs, such as SC-specific over-expression of the microtubule nucleating protein, gamma-tubulin [11], [12], or SC-specific expression of a dominant-negative form of the microtubule plus end binding protein EB1 [13] induce similar germ cell loss from the seminiferous epithelium. Together these studies demonstrate that SC microtubule-dependent functions are extremely sensitive to aberrant microtubule remodelling.…”
Section: Introductionmentioning
confidence: 99%
“…Di-(n-butyl)-phthalate (DBP) is a Sertoli cell toxicant (Gray et al, 1982;Gray and Beamand, 1984). Nitrofurazone is a seminiferous tubule germ cell toxicant that causes single strand DNA breakage and damage loss of round spermatocytes and elongate spermatids (Olive and McCalla, 1975;Nishimura et al, 1995;Shoda et al, 2001;Hagenas et al, 2009), 2,5-hexanedione (2,5-HD) is a neurotoxicant that also disrupts spermiation with findings including Sertoli cell vacuolation, spermatid retention, and complete depletion of germ cells (Boekelheide, 1988;Fleming et al, 2003;Moffit et al, 2007). The fungicide carbendazim (CBZ) disrupts Sertoli cell microtubules resulting in abnormal spermatocytes and spermatids with giant and multinucleate spermatids (Carter et al, 1987;Nakai et al, 1992Nakai et al, , 1997Nakai and Hess, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…First, intra-testicular injection via the efferent ductules or rete testis has been used for many years as a means of transferring germ stem cells from a donor testis into the seminiferous epithelium of a recipient (Ogawa et al 1997, 2000) and members of our team had successfully performed this technique. Second, previous studies have reported the use of adenoviral vectors to introduce transgenes into the testes of adult rats (Blanchard & Boekelheide 1997, Scobey et al 2001, Fleming et al 2003 a , 2003 b ) and mice (Kanatsu-Shinohara et al 2002). In the rat expression of the transgene was confined to SC and persisted for up to 10 days after injection (Blanchard & Boekelheide 1997, Scobey et al 2001).…”
Section: Introductionmentioning
confidence: 99%